Functional disabilities and its associated factors among elderly patients in primary care clinics - Md Aris, Mohd Aznan; Draman, Samsul; Ab Rahman, Jamalludin; Samsuddin, Niza (Faculty of Medicine, International Islamic University Malaysia, 2009)
Introduction: Identification of risk factors associated with functional disability among elderly population is important in order to improve their quality of life.